Changes in the total knee joint moment in patients with medial compartment knee osteoarthritis over 5 years. Issue 9 (25th April 2018) - Asay, Jessica L.; Erhart‐Hledik, Jennifer C.; Andriacchi, Thomas P.
ABSTRACT: Progression of medial compartment knee osteoarthritis (OA) has been associated with repetitive mechanical loading during walking, often characterized by the peak knee adduction (KAM) and knee flexion moments (KFM). However, the relative contributions of these components to the knee total joint moment (TJM) can change as the disease progresses since KAM and KFM are influenced by different factors that change over time. This study tested the hypothesis that the relative contributions of KAM, KFM, and the rotational moment (KRM) to the TJM change over time in subjects with medial compartment knee OA. Patients with medial compartment knee OA ( n  = 19) were tested walking at their self‐selected speed at baseline and a 5‐year follow‐up. For each frame during stance, the TJM was calculated using the KAM, KFM, and KRM. The peaks of the TJM and the relative contributions of the moment components at the time of the peaks of the TJM were tested for changes between baseline and follow‐up. The percent contribution of KFM to the first peak of the TJM (TJM1) significantly decreased ( p  < 0.001) and the percent contribution of KAM to TJM1 significantly increased ( p  <  0.001), while the magnitude of the TJM1 did not significantly change over the 5‐year follow‐up. These gait changes with disease progression appear to maintain a constant TJM1, but the transition from a KFM to a KAM dominance appears to reflect gait changes associated with progressing OA and pain. Thus, the TJM and its component analysis captures a comprehensive metric for total loading on the knee over time. Published 2018. This article is a U.S. Government work and is in the public domain in the USA. 36:2373–2379, 2018.